Degradable repair patch and preparation method and application thereof

Through the composite preparation method of multi-layer fiber orientation sheets, electrospinning method is used to form a degradable repair patch with cross-structure, which solves the problems of poor biocompatibility and poor mechanical strength of existing patches, and achieves efficient cell migration and proliferation, which is suitable for repair of various tissues.

CN119746156APending Publication Date: 2025-04-04SUZHOU RUIJINUO MEDICAL TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411995587.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing degradable repair patches have problems such as poor biocompatibility, poor mechanical strength and uncontrollable degradation time, which may cause inflammatory responses and tissue fibrosis in the body for too long.

Method used

The multilayer fiber orientation sheet was prepared by composite preparation, and the oriented fibers were formed by electrospinning. The diameter of the fiber orientation sheet was 1 nm to 20 μm and the porosity was 40 to 80%. The cross structure was formed by adjusting the fiber orientation direction, thereby improving the mechanical properties and biocompatibility of the patch.

Benefits of technology

It has achieved good cell mobility and proliferation rate of degradable repair patches, with better mechanical strength and biocompatibility, and has controllable degradation time, which is suitable for nerve, blood vessel, oral and bone tissue repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746156A_ABST
    Figure CN119746156A_ABST
Patent Text Reader

Abstract

The present invention provides a degradable repair patch and its preparation method and application, which relate to the technical field of medical repair materials. The degradable repair patch is prepared by compounding multiple layers of fiber-oriented sheets. Wherein: the fiber-oriented sheet is formed into oriented fibers by electrostatic spinning, the orientation direction of the oriented fibers in the fiber-oriented sheet is consistent, and the orientation directions of the oriented fibers in each layer of fiber-oriented sheets in the repair patch are different. The oriented fiber structure prepared by the electrostatic spinning method of the present invention is conducive to cell migration, and the prepared patch has good cell migration rate and high growth rate. At the same time, the patch prepared by compounding fiber-oriented sheets with different orientation directions has better mechanical strength and is not easy to be torn. In addition, the oriented fiber diameter in the fiber-oriented sheet of the present application is 1nm to 20μm, and the porosity is 40 to 80%, which makes it easier for cells to attach to the fiber, which is conducive to cell proliferation and growth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical repair materials, and in particular to a degradable repair patch and a preparation method and application thereof. Background Art

[0002] In recent years, with the rapid development of transplantation medicine and alternative medicine, degradable repair patches have been widely used in clinical practice due to their advantages of being absorbable by the human body. Existing degradable repair patches include animal-derived patches and degradable synthetic material patches based on the source of the material. However, animal-derived patches have potential immunogenicity or viral infection risks, and their rapid degradation rate in the body leads to a shorter support time, and their mechanical strength is insufficient, making them easily damaged when subjected to greater pressure or tension; existing degradable synthetic material patches often have problems of poor biocompatibility and poor mechanical strength, resulting in unsatisfactory repair effects. In addition, currently, most of the degradable synthetic material patches at home and abroad are made of polyglycolic acid, polyglycolic acid-carbonate or polylactic acid, but the degradation time is uncontrollable. In order to ensure that the patch maintains sufficient mechanical strength before the tissue is completely repaired, its degradation cycle in the body is much longer than the tissue repair cycle. If the patch exists in the body for too long, it may stimulate the surrounding tissues, leading to inflammatory reactions, and may also induce tissue fibrosis, resulting in increased hardness of the surrounding tissues and affecting normal functions.

[0003] Therefore, it is necessary and urgent to research and develop a degradable repair patch with better biocompatibility, mechanical strength and controllable degradation time.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first purpose of the present invention is to provide a degradable repair patch, which has the technical advantages of good cell migration rate, good mechanical strength, and cells are more easily attached to fibers, which is beneficial to cell proliferation and growth.

[0006] The second object of the present invention is to provide a method for preparing a degradable repair patch.

[0007] The third object of the present invention is to provide an application of a degradable repair patch.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] The present invention provides a degradable repair patch, which is prepared by compounding multiple layers of fiber oriented sheets;

[0010] The fiber orientation sheet is formed into oriented fibers by an electrostatic spinning method, and the orientation directions of the oriented fibers in the fiber orientation sheet are consistent;

[0011] The diameter of the oriented fibers in the fiber orientation sheet is 1 nm to 20 μm, the porosity is 40 to 80%, and the thickness of the fiber orientation sheet is 0.05 to 0.95 mm;

[0012] The orientation directions of the fibers in each layer of the fiber orientation sheets in the degradable repair patch are different.

[0013] Furthermore, the oriented fibers are obtained by electrostatic spinning of degradable polyurethane or polylactic acid.

[0014] Preferably, the weight average molecular weight Mw of the degradable polyurethane is 20W to 26W;

[0015] Preferably, the weight average molecular weight Mw of the polylactic acid is 15W to 30W.

[0016] Furthermore, the thickness of the degradable repair patch is 0.1-1 mm, the tensile strength is 10N / cm-50N / cm, the elongation at break is 100%-800%, and the suture strength is 5N-30N.

[0017] Furthermore, the multi-layer fiber oriented sheet includes 2 to 6 layers, preferably 2 layers.

[0018] Furthermore, the degradable repair patch is prepared by compounding two layers of fiber oriented sheets;

[0019] Preferably, the two-layer fiber-oriented sheet comprises a first fiber-oriented sheet and a second fiber-oriented sheet, and the first fiber-oriented sheet and the second fiber-oriented sheet have different orientation directions and are at an angle of 90°±15°.

[0020] The present invention provides a method for preparing the above-mentioned degradable repair patch, the method comprising:

[0021] S1: dissolving the degradable polyurethane in a solvent to obtain a spinning solution;

[0022] S2: electrospinning the spinning solution to obtain a fiber orientation sheet A, then adjusting the electrospinning direction, electrospinning on the fiber orientation sheet A to obtain a fiber orientation sheet B intersecting the orientation direction of the fiber orientation sheet A, and obtaining a degradable repair patch composed of two layers of fiber orientation sheets;

[0023] S3: repeat step S2 to obtain a degradable repair patch composed of multiple layers of fiber oriented sheets;

[0024] Preferably, in step 2, the orientation directions of the fiber orientation sheet A and the fiber orientation sheet B are perpendicularly crossed at an angle of 90°±15°.

[0025] Furthermore, in step S1, the concentration of the degradable polyurethane in the spinning solution is 5 to 25% (w / v);

[0026] Preferably, the solvent in the spinning solution is a single solvent of N,N-dimethylformamide, a single solvent of N,N-dimethylacetamide, a mixed solvent of N,N-dimethylformamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether, or a mixed solvent of N,N-dimethylacetamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether;

[0027] More preferably, the solvent in the spinning solution is a mixed solvent of N,N-dimethylformamide and tetrahydrofuran, wherein the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 10:1-3:7, wherein the preferred volume ratio is 10:1-1:1.

[0028] Furthermore, the electrospinning conditions in step S2 include:

[0029] Negative voltage: -1KV~-4KV, positive voltage: 8KV~10KV, injection speed of the nozzle: 0.05-0.6ml / min; rotation speed of the receiving device: (800, 2800)rpm / min, distance between the nozzle and the receiving device: 0~50mm; translation speed of the nozzle is (0, 500)mm / min.

[0030] Furthermore, the preparation method also includes: a step of removing the solvent from the prepared degradable repair patch.

[0031] The fiber-oriented sheet in the degradable repair patch provided by the present invention is used in the preparation of nerve tissue repair materials, vascular tissue repair materials, oral tissue repair materials and bone tissue repair materials.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The degradable repair patch provided by the present invention is prepared by compounding multiple layers of fiber-oriented sheets. Wherein: the fiber-oriented sheets are formed into oriented fibers by electrostatic spinning, the orientation directions of the oriented fibers in the fiber-oriented sheets are consistent, and the orientation directions of the oriented fibers in each layer of fiber-oriented sheets compounded in the repair patch are different. The oriented fiber structure prepared by the electrostatic spinning method of the present invention is conducive to cell migration, and the obtained patch has good cell migration rate and high growth rate. At the same time, the patch prepared by compounding fiber-oriented sheets with different orientation directions has better mechanical strength and is not easy to be torn. In addition, the fiber-oriented sheets of the present application have an oriented fiber diameter of 1nm to 20μm and a porosity of 40 to 80%, so that cells are more easily attached to the fibers, which is conducive to cell proliferation and growth.

[0034] The fiber-oriented sheet in the degradable repair patch provided by the present invention can be widely used in the preparation process of nerve tissue repair materials, vascular tissue repair materials, oral tissue repair materials and bone tissue repair materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 This is a scanning electron microscope image of the first fiber-oriented sheet of the degradable repair patch prepared by the two-layer fiber-oriented sheet of the present invention;

[0037] Figure 2 This is a scanning electron microscope image of the second fiber-oriented sheet of the degradable repair patch prepared by the two-layer fiber-oriented sheet of the present invention;

[0038] Figure 3 This is a diagram showing the cell migration results of the cells provided in Experimental Example 1 of the present invention and the degradable repair patch of Example 1 of the present application. DETAILED DESCRIPTION

[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] According to one aspect of the present invention, a degradable repair patch is prepared by compounding multiple layers of fiber oriented sheets;

[0041] The fiber orientation sheet is formed into oriented fibers by an electrostatic spinning method, and the orientation directions of the oriented fibers in the fiber orientation sheet are consistent;

[0042] The diameter of the oriented fibers in the fiber orientation sheet is 1 nm to 20 μm, the porosity is 40 to 80%, and the thickness of the fiber orientation sheet is 0.05 to 0.95 mm;

[0043] The orientation directions of the fibers in each layer of the fiber orientation sheets in the degradable repair patch are different.

[0044] The degradable repair patch provided by the present invention is prepared by compounding multiple layers of fiber-oriented sheets. Wherein: the fiber-oriented sheets are formed into oriented fibers by electrostatic spinning, the orientation directions of the oriented fibers in the fiber-oriented sheets are consistent, and the orientation directions of the oriented fibers in each layer of fiber-oriented sheets compounded in the repair patch are different. The oriented fiber structure prepared by the electrostatic spinning method of the present invention is conducive to cell migration, and the obtained patch has good cell migration rate and high cell growth rate. At the same time, the patch prepared by compounding fiber-oriented sheets with different orientation directions has better mechanical strength and is not easy to be torn. In addition, the fiber-oriented sheets of the present application have an oriented fiber diameter of 1nm to 20μm and a porosity of 40 to 80%, so that cells are more easily attached to the fibers, which is conducive to cell proliferation and growth.

[0045] It is important to note that during tissue repair in the body, such as during hernia repair, there are multiple types of cells involved in healing and reconstruction. The sizes of the different types of cells are generally as follows: Fibroblasts: These cells play a key role in hernia repair and are responsible for synthesizing collagen and extracellular matrix. Fibroblasts are generally between 20 and 70 microns in diameter. Macrophages: They are involved in inflammatory responses and the removal of dead cells and are generally between 10 and 30 microns in diameter. Macrophages help regulate cell proliferation and tissue reconstruction during the repair process. Endothelial cells: During hernia repair, endothelial cells are responsible for the formation of new blood vessels and are generally between 10 and 25 microns in diameter. The new blood vessels provide nutrients and oxygen to support the healing process. Smooth muscle cells: At the repair site, smooth muscle cells can participate in rebuilding the structure of the abdominal wall and are generally between 10 and 20 microns in diameter. Lymphocytes: As part of the immune response, lymphocytes are generally between 7 and 10 microns in diameter and are involved in regulating local inflammatory responses. The interaction and coordination of these cells during hernia repair is key to ensuring wound healing and restoration of function after surgery.

[0046] At the same time, it has been found that the above-mentioned cells have better adhesion properties on fibers with a diameter smaller than their own during hernia repair. When the transverse diameter of the electrospinning is controlled to be smaller than the cell diameter, it is beneficial for the cells to attach and grow on the electrospinning. Since most of the cells in the hernia repair tissue are fibroblasts, the size of fibroblasts is 20-70 microns. When using electrospinning to make hernia repair patches, the transverse diameter range of the electrospinning is controlled to be less than 20 microns. In addition, the present application has found that sufficient pores (40-80%) in the sheet are more conducive to cell growth and proliferation. After the pores in the sheet are filled with new cells, the fibers gradually degrade, which frees up new space for the cells to further proliferate and new tissue to form.

[0047] Therefore, the diameter of the oriented fibers in the fiber oriented sheet of the present application is 1 nm to 20 μm, the porosity is 40 to 80%, and the thickness of the fiber oriented sheet is 0.05 to 0.95 mm;

[0048] As a preferred embodiment, the diameter of the oriented fibers in the fiber oriented sheet of the present application is controlled to be less than 10 microns, thereby achieving a better repair effect.

[0049] The diameter of the oriented fiber may be, but is not limited to, 1 nm, 10 nm, 50 nm, 80 nm, 100 nm, 200 nm, 350 nm, 500 nm, 700 nm, 900 nm, 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, 13 μm, 15 μm, 18 μm or 20 μm, or any value between 1 nm and 20 μm. The porosity of the oriented fiber may be, but is not limited to, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, or any proportion between 40% and 80%. The thickness of the fiber oriented sheet may be, but is not limited to, 0.05 mm, 0.15 mm, 0.25 mm, 0.35 mm, 0.45 mm, 0.55 mm, 0.65 mm, 0.75 mm, 0.85 mm or 0.95 mm, and may be any value between 0.05 mm and 0.95 mm.

[0050] In a preferred embodiment of the present invention, the oriented fibers are obtained by electrostatic spinning of degradable polyurethane or polylactic acid.

[0051] In the above preferred embodiment, the weight average molecular weight Mw of the degradable polyurethane is 20W to 26W; the weight average molecular weight Mw of the polylactic acid is 15W to 30W.

[0052] As a preferred embodiment, the fiber oriented sheet prepared by the degradable polyurethane or polylactic acid with the above molecular weight in the present application has better mechanical strength and softness.

[0053] The weight average molecular weight of the degradable polyurethane may be, but not limited to, 20W, 21W, 22W, 23W, 24W, 25W or 26W, or any value between 20W and 26W. The weight average molecular weight of the polylactic acid may be, but not limited to, 15W, 16W, 17W, 18W, 19W, 20W, 21W, 22W, 23W, 24W, 25W, 26W, 27W, 28W, 29W or 30W, or any value between 15W and 30W.

[0054] In a preferred embodiment of the present invention, the thickness of the degradable repair patch is 0.1-1 mm, the tensile strength is 10N / cm-50N / cm, the elongation at break is 100%-800%, and the suture strength is 5N-30N.

[0055] In a preferred embodiment of the present invention, the multi-layer fiber oriented sheet comprises 2 to 6 layers, preferably 2 layers.

[0056] In a preferred embodiment of the present invention, the degradable repair patch is prepared by compounding two layers of fiber oriented sheets;

[0057] The two-layer fiber-oriented sheet comprises a first fiber-oriented sheet and a second fiber-oriented sheet. The first fiber-oriented sheet and the second fiber-oriented sheet have different orientation directions and are oriented at an angle of 90°±15°.

[0058] Figure 1 This is a scanning electron microscope image of the first fiber-oriented sheet of the degradable repair patch prepared from the two-layer fiber-oriented sheets of the present invention.

[0059] Figure 2 This is a scanning electron microscope image of the second fiber-oriented sheet of the degradable repair patch prepared from the two-layer fiber-oriented sheets of the present invention.

[0060] Wherein: the orientation directions of the first fiber orientation sheet and the second fiber orientation sheet are at an angle of 90°±15°.

[0061] Depend on Figure 1 , Figure 2 It can be seen that in the degradable repair patch prepared by the two-layer fiber orientation sheet of the present application, the orientation directions of the first fiber orientation sheet and the second fiber orientation sheet are in a vertically crossed or nearly vertically crossed structural form.

[0062] As a preferred embodiment, the present application has found through research that a degradable repair patch prepared by a composite of two layers of fiber-oriented sheets "wherein the orientation directions of the first fiber-oriented sheet and the second fiber-oriented sheet are different and are at an angle of 90°±15°" has better mechanical strength than a degradable repair patch in which both layers have the same orientation direction.

[0063] In a preferred embodiment of the present invention, the degradable repair patch is prepared by compounding two layers of fiber oriented sheets;

[0064] The two-layer fiber-oriented sheet comprises a first fiber-oriented sheet and a second fiber-oriented sheet. The first fiber-oriented sheet and the second fiber-oriented sheet have different orientation directions and are oriented at an angle of 90°±15°.

[0065] Mainly manifested in:

[0066] 1. The degradable repair patch prepared by the above two layers of fiber oriented sheets has a better cell proliferation rate than the multi-layer structure. This is because in the multi-layer structure, cell proliferation is easy to cross layers, that is, some cells will proliferate in the direction of the thickness of the patch instead of spreading along the orientation direction, which affects the cell proliferation to a certain extent. This situation is not conducive to the speed of tissue repair. At the same time, the porosity of the degradable repair patch obtained by the two layers of fiber oriented sheets is easier to repair the combination of cells and the patch, and the biocompatibility is better; at the same time, the cell migration rate is good and the cell growth rate is high.

[0067] 2. The degradable repair patch prepared by two layers of fiber oriented sheets with a vertical or nearly vertical cross structure has good transverse and longitudinal mechanical strength and is not easily torn.

[0068] 3. The degradable repair patch obtained by two layers of fiber-oriented sheets is thinner and has a wider applicability; the degradation cycle is suitable for tissue repair that requires a shorter degradation cycle. It can be effectively degraded after forming tissue engineering support, and there will be no problem of long degradation time affecting tissue healing.

[0069] According to one aspect of the present invention, a method for preparing the above-mentioned degradable repair patch comprises:

[0070] S1: dissolving the degradable polyurethane in a solvent to obtain a spinning solution;

[0071] S2: electrospinning the spinning solution to obtain a fiber orientation sheet A, then adjusting the electrospinning direction, electrospinning on the fiber orientation sheet A to obtain a fiber orientation sheet B intersecting the orientation direction of the fiber orientation sheet A, and obtaining a degradable repair patch composed of two layers of fiber orientation sheets;

[0072] S3: repeat step S2 to obtain a degradable repair patch composed of multiple layers of fiber oriented sheets;

[0073] Preferably, in step 2, the orientation directions of the fiber orientation sheet A and the fiber orientation sheet B are perpendicularly crossed at an angle of 90°±15°.

[0074] The preparation method of the degradable repair patch provided by the present invention comprises the following steps: electrostatically spinning a degradable polyurethane spinning solution to obtain a fiber orientation sheet A, and then adjusting the electrostatic spinning direction to composite a plurality of fiber orientation sheets intersecting the orientation direction of the fiber orientation sheet A onto the fiber orientation sheet A, thereby obtaining a degradable repair patch composed of the plurality of fiber orientation sheets. The preparation method has the advantages of simple processing technology and easy operation.

[0075] It should be noted that the present invention has no special restrictions on the composite method of the multi-layer fiber oriented sheet, as long as the composite of the multi-layer fiber oriented sheet can be achieved. For example, the optional method may also be: electrospinning the spinning solution to obtain a plurality of fiber oriented sheets; stacking and pressing the plurality of fiber oriented sheets on the premise that the orientation directions of the fiber oriented sheets of each layer are cross-arranged to obtain a degradable repair patch.

[0076] In a preferred embodiment of the present invention, the concentration of the degradable polyurethane in the spinning solution in step S1 is 5 to 25% (w / v);

[0077] Preferably, the solvent in the spinning solution is a single solvent of N,N-dimethylformamide, a single solvent of N,N-dimethylacetamide, a mixed solvent of N,N-dimethylformamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether, or a mixed solvent of N,N-dimethylacetamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether;

[0078] More preferably, the solvent in the spinning solution is a mixed solvent of N,N-dimethylformamide and tetrahydrofuran, wherein the volume ratio of N,N-dimethylacetamide to tetrahydrofuran can be but not limited to 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 3:1 or 3:7, and can also be any ratio between 10:1 and 3:7, preferably 10:1 to 1:1.

[0079] In a preferred embodiment of the present invention, the conditions for electrospinning in step S2 include:

[0080] Negative voltage: -1KV~-4KV, positive voltage: 8KV~10KV, injection speed of the nozzle: 0.05-0.6ml / min; rotation speed of the receiving device: (800, 2800)rpm / min, distance between the nozzle and the receiving device: 0~50mm; translation speed of the nozzle is (0, 500)mm / min.

[0081] In a preferred embodiment of the present invention, the preparation method further comprises: a step of removing the solvent from the prepared degradable repair patch.

[0082] According to one aspect of the present invention, the fiber-oriented sheet in the above-mentioned degradable repair patch can be widely used in the preparation process of nerve tissue repair materials, vascular tissue repair materials, oral tissue repair materials and bone tissue repair materials.

[0083] The technical solution of the present invention will be further described below in conjunction with embodiments.

[0084] Example 1 (double layer, first spin one layer, rotate 90 degrees in the middle, and then spin another layer)

[0085] A method for preparing a degradable repair patch, the method comprising:

[0086] 1. Preparation of degradable polyurethane (PU) solution:

[0087] A 25% polyurethane solution was prepared by using a degradable polyurethane (weight average molecular weight Mw of 20W) as a solute and a mixed solution of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) as a solvent.

[0088] The ratio of solvent: tetrahydrofuran (THF): N,N-dimethylformamide (DMF) = 1:1.

[0089] The specific preparation operation is as follows:

[0090] (1) Add 150 mL of tetrahydrofuran and 150 mL of N,N-dimethylformamide into a three-necked flask, turn on the stirrer, adjust the speed to (200 ± 100) r / min, and stir evenly.

[0091] (2) Weigh 75 g of polyurethane material and add it to a three-necked flask. Different volumes of solution can be prepared according to the amount of solution used.

[0092] (3) Stir at room temperature for more than 4 hours to completely dissolve the PU. Let stand for more than 4 hours to remove bubbles and set aside.

[0093] 2. Electrospinning:

[0094] (1) Wipe the electrospinning machine clean and ensure that the equipment is in a clean state.

[0095] (2) Fix the release paper on the receiving device to ensure that the release paper is not loose.

[0096] (3) Adjust the distance between the nozzle and the receiver to 20±1cm, determine the position and tighten it.

[0097] (4) The receiver receiving speed is set to (1500±100) rpm / min; the injection speed of the nozzle is set to 0.3±0.05 ml / min.

[0098] (5) The translation speed of the nozzle is set to 450±50mm / min, and the translation distance is set to 300±50mm.

[0099] (6) Use the prepared 25% PU solution and slowly draw the PU solution with a disposable syringe to avoid bubbles. If bubbles are generated, they must be removed before subsequent operations. Install a 22G needle (inner diameter 0.41mm) and fix the syringe in the buckle of the electrospinning machine push pump.

[0100] The nozzle diameter range can be: 0.15-4.2mm, preferably 18G (inner diameter 0.9mm), 19G (inner diameter 0.84mm), 20G (inner diameter 0.62mm), 21G (inner diameter 0.51mm), 22G (inner diameter 0.41mm), 23G (inner diameter 0.33mm), 24G (inner diameter 0.3mm) needles. In this embodiment, a 22G needle is selected.

[0101] (7) Set the negative voltage to (-3±1) KV and the positive voltage to (9±0.5) KV. Start electrospinning and observe the spinning effect until continuous and uniform filaments are ejected. Set the electrospinning time to 30 min to 1 h. After the first electrospinning, rotate the release paper (with a spinning layer on the surface) 90 degrees and then fix it. Set the electrospinning time to 30 min to 1 h again and repeat the operation for the second electrospinning.

[0102] After the second electrospinning, the electrospun membrane was removed from the release paper.

[0103] 3. Post-processing:

[0104] (1) Soak the electrospun membrane in a water tank for at least 7 days, changing the water twice a day and cleaning it every two days.

[0105] The ratio of the patch surface area to the water volume in each water tank should be ≥900cm 2 / L.

[0106] (2) Rinse the electrospun membrane with injection water cooled to 30°C and lay it flat on the partition rack of the oven.

[0107] The oven temperature was set at 35°C and the drying time was (5±1) h. After the electrospun membrane was dried, the appearance was inspected and then cut into degradable repair patches of the required size.

[0108] The thickness of the degradable repair patch of this embodiment is 0.25±0.05 mm, the diameter of the oriented fibers of the single-layer fiber oriented sheet is 1 nm to 20 μm, and the porosity is 60±10%.

[0109] Example 2 (four layers, first spinning one layer, rotating 90 degrees in the middle, and then spinning another layer, repeating until a four-layer structure of a degradable repair patch is formed)

[0110] In this embodiment, except for step 2 electrospinning (7), the following steps are performed:

[0111] “(7) The negative voltage is set to (-3±1) KV, and the positive voltage is set to (9±0.5) KV. Start electrospinning and observe the spinning effect until continuous and uniform filaments are ejected. Set the electrospinning time to 30 min to 1 h. After the first electrospinning, rotate the release paper (with a spinning layer on the surface) 90 degrees and then fix it. Set the electrospinning time to 30 min to 1 h again, and repeat the operation for the second electrospinning.

[0112] After the second electrospinning is completed, the release paper (with a spinning layer on the surface) is rotated 90 degrees and then fixed to set the electrospinning time to 30 minutes to 1 hour, and the operation is repeated for the third electrospinning.

[0113] After the third electrospinning, the release paper (with a spinning layer on the surface) was rotated 90 degrees and then fixed to set the electrospinning time to 30 minutes to 1 hour, and the operation was repeated for the fourth electrospinning. ", the rest is the same as in Example 1.

[0114] The thickness of the degradable repair patch of this embodiment is 0.55±0.05 mm, the diameter of the oriented fibers of the single-layer fiber oriented sheet is 1 nm to 20 μm, and the porosity is 60±10%.

[0115] Example 3 (six layers, first spin one layer, rotate 90 degrees in the middle, then spin another layer, repeat until a six-layer structured degradable repair patch is formed)

[0116] In this embodiment, except for step 2 electrospinning (7), the following steps are performed:

[0117] “(7) The negative voltage is set to (-3±1) KV, and the positive voltage is set to (9±0.5) KV. Start electrospinning and observe the spinning effect until continuous and uniform filaments are ejected. Set the electrospinning time to 30 min to 50 min. After the first electrospinning, rotate the release paper (with a spinning layer on the surface) 90 degrees and then fix it. Set the electrospinning time to 30 min to 50 min again, and repeat the operation for the second electrospinning.

[0118] After the second electrospinning is completed, the release paper (with a spinning layer on the surface) is rotated 90 degrees and then fixed to set the electrospinning time to 30 minutes to 50 minutes, and the operation is repeated for the third electrospinning.

[0119] After the third electrospinning, the release paper (with a spinning layer on the surface) was rotated 90 degrees and then fixed to set the electrospinning time to 30 min to 50 min, and the operation was repeated for the fourth electrospinning.

[0120] After the fourth electrospinning, the release paper (with a spinning layer on the surface) was rotated 90 degrees and then fixed to set the electrospinning time to 30 min to 50 min, and the operation was repeated for the fifth electrospinning.

[0121] After the fifth electrospinning, the release paper (with a spinning layer on the surface) was rotated 90 degrees and then fixed to set the electrospinning time to 30 min to 50 min, and the operation was repeated for the sixth electrospinning. The rest was the same as in Example 1.

[0122] The thickness of the degradable repair patch of this embodiment is 0.95±0.05 mm, the diameter of the oriented fibers of the single-layer fiber oriented sheet is 1 nm to 20 μm, and the porosity is 60±10%.

[0123] Example 4 (double layer, first spin one layer, rotate 45 degrees in the middle, and then spin another layer)

[0124] In this embodiment, except for step 2 electrospinning (7), the following steps are performed:

[0125] “(7) The negative voltage is set to (-3±1) KV, and the forward voltage is set to (9±0.5) KV. Start electrospinning and observe the spinning effect until continuous and uniform filaments are ejected. Set the electrospinning time to 30 min to 1 h. After the first electrospinning is completed, rotate the release paper (with a spinning layer on the surface) 45 degrees and then fix it. Set the electrospinning time to 30 min to 1 h again, and repeat the operation for the second electrospinning.” The rest is the same as Example 1.

[0126] Example 5 (six layers, first spin one layer, rotate 45 degrees in the middle, then spin another layer, repeat until a six-layer structured degradable repair patch is formed)

[0127] In this embodiment, except for step 2 electrospinning (7), the following steps are performed:

[0128] “(7) The negative voltage is set to (-3±1) KV, and the positive voltage is set to (9±0.5) KV. Start electrospinning and observe the spinning effect until continuous and uniform filaments are ejected. Set the electrospinning time to 30 min to 50 min. After the first electrospinning, rotate the release paper (with a spinning layer on the surface) 45 degrees and then fix it. Set the electrospinning time to 30 min to 50 min again, and repeat the operation for the second electrospinning.

[0129] After the second electrospinning, the release paper (with a spinning layer on the surface) was rotated 45 degrees and then fixed to set the electrospinning time to 30 min to 50 min, and the operation was repeated for the third electrospinning.

[0130] After the third electrospinning, the release paper (with a spinning layer on the surface) was rotated 45 degrees and then fixed to set the electrospinning time to 30 min to 50 min, and the operation was repeated for the fourth electrospinning.

[0131] After the fourth electrospinning, the release paper (with a spinning layer on the surface) was rotated 45 degrees and then fixed to set the electrospinning time to 30 min to 50 min, and the operation was repeated for the fifth electrospinning.

[0132] After the fifth electrospinning, the release paper (with a spinning layer on the surface) was rotated 45 degrees and then fixed to set the electrospinning time for 30 min to 50 min, and the operation was repeated for the sixth electrospinning. The rest was the same as in Example 3.

[0133] Example 6 (double layer, first spin one layer, rotate 90 degrees in the middle, and then spin another layer)

[0134] Polylactic acid (weight average molecular weight Mw: 25W) was used as the solute, and the rest was the same as in Example 1.

[0135] Comparative Example 1 (double layer, fibers in the patch do not have an oriented structure)

[0136] A method for preparing a degradable repair patch, the method comprising:

[0137] 1. Preparation of degradable polyurethane (PU) solution: same as Example 1.

[0138] 2. Electrospinning: Except that the rotation speed of the receiving device is (0, 800) rpm / min, other process parameters are the same as those in Example 1.

[0139] In this comparative example, when the rotating speed of the receiving device is lower than 800 rpm / min, the spun sheet produced does not have oriented structural fibers.

[0140] 3. Post-processing: same as Example 1.

[0141] Comparative Example 2 (double-layer, the orientation directions of the two fiber orientation sheets in the patch are the same)

[0142] In this comparative example, except for step 2 electrospinning (7), the following is performed:

[0143] “(7) The negative voltage is set to (-3±1) KV, and the positive voltage is set to (9±0.5) KV. Start electrospinning and observe the spinning effect until continuous and uniform filaments are ejected. Set the electrospinning time to 30 min to 1 h. After the first electrospinning, keep the release paper (with a spinning layer on the surface) fixed without rotating. Set the electrospinning time to 30 min to 1 h again, and repeat the operation for the second electrospinning.

[0144] After the second electrospinning was completed, the electrospinning membrane was removed from the release paper. The rest was the same as in Example 1.

[0145] Test Example 1

[0146] (I) Mechanical properties test:

[0147] Experimental methods:

[0148] (1) Tensile strength: First, cut the dry sample to be tested into multiple specimens with appropriate width, flat edges, parallel sides and no visible defects, then turn on the tensile testing machine, set the parameters, perform the tensile strength test, and process the data. Tensile strength (N / cm) = tension (N) / specimen width (cm).

[0149] (2) Elongation at break: First, cut the dry sample to be tested into multiple specimens with appropriate width, flat edges, parallel sides and no visible defects. Then turn on the tensile testing machine, set the parameters, perform the elongation at break test, and process the data; elongation at break (%) = (elongation at break of specimen / original length of specimen) × 100%.

[0150] (3) Suture strength: First, cut the dry sample to be tested into multiple specimens with appropriate width, flat edges, parallel sides and no visible defects. Then, use a suture thread of the selected specification to sew one end of the sample to be tested with two needles and tie a knot to fix it. Suture multiple specimens in the same way, and test the thickness of each sample with a thickness gauge. Then, use a tensile testing machine to clamp the sample to be tested and test the suture strength of the suture to obtain the test data.

[0151] (4) Tear strength: First, cut the dry sample to be tested into samples with appropriate width, flat edges, parallel sides and no visible defects. Use a cutter to cut along the center of the sample to prepare a trouser-shaped sample. The cutting edge of the cutter must be sharp and must not have curled edges or gaps. The cut is located in the center of the sample width. Use a thickness gauge to measure 3 points in the tear area of ​​the sample, and the arithmetic average is the thickness. Turn on the tensile testing machine, clamp the sample to be tested, and perform a tear strength test to obtain the test data.

[0152] (5) Bursting strength: First, cut the dry sample to be tested into multiple square specimens with appropriate width, flat edges, parallel sides and no visible defects, and use a thickness gauge to test the thickness of each sample. Then, turn on the tensile testing machine, clamp the sample to be tested, and perform the bursting strength test to obtain the test data.

[0153] Experimental results:

[0154]

[0155] It can be seen from the above results that compared with the fiber oriented sheet in a single orientation direction, the fiber oriented sheet in a cross orientation direction has better mechanical strength in both the longitudinal and transverse directions. The tensile strength of the degradable repair patch of the present invention reaches 12.55-51.33N / cm, the elongation at break reaches 109.54-802.61%, the suture strength reaches 5.03-32.06N, the tear strength reaches 10.98-63.09N, and the bursting strength reaches 103.56-516.09kPa. The degradable repair patch of the present invention has good mechanical properties and can well meet the mechanical property requirements of the patch for tissue repair.

[0156] (II) Cell proliferation assay:

[0157] Experimental methods:

[0158] Each sample was made into a circular specimen of the same size as the bottom area of ​​a 48-well plate using a puncher. After sterilization, it was placed in a 48-well cell culture plate and immersed in MEM medium containing 10% FBS at 37°C and 60 rpm for 24 hours, with the outer layer of the specimen facing the bottom of the well.

[0159] The whole process was performed in a clean bench to ensure aseptic operation. Mouse fibroblast L-929 cells grown to the logarithmic growth phase were digested with 0.25% trypsin (containing EDTA), and the cell suspension was centrifuged (1000rpm, 5min) after digestion, the supernatant was discarded, and the cells were resuspended with MEM medium, and the cells were counted to obtain a cell suspension of 2×104 cells / mL; the soaked samples were respectively spread in 48-well plates, and 3 samples were operated in parallel in each group.

[0160] 2×10 4 300 μL of a cell suspension of 10 cells / mL was seeded into each well of a 48-well plate and cultured in a cell culture incubator (37° C., 5% CO 2 , >90% humidity).

[0161] After 24h, 3d and 6d, the original culture medium in the 48-well plate was discarded, and 30μL of MTT solution (concentration of 5mg / mL) was added to the corresponding wells of the 48-well plate, and cultured in a 37°C, 5% carbon dioxide incubator. After 4h, the supernatant was removed, and 200μL of isopropanol was added to each well to dissolve the crystals. After the crystals were completely dissolved, the sample was taken out and the liquid in the well was transferred to a 96-well plate, 100μL per well, and the absorbance value at a wavelength of 570nm was measured on an enzyme reader, and compared with the OD value of the blank group to determine whether the cells had a proliferation effect on the surface of the material and calculate its cell proliferation rate.

[0162] Experimental results:

[0163]

[0164]

[0165] From the above results, it can be seen that Examples 1 to 6 have very good cell proliferation rate effects, especially the cell proliferation rate effects of the two-layer fiber oriented sheets of Examples 1, 4, and 6 are more significant. This is because the cell proliferation rate of the two-layer degradable repair patch is better, while the cell proliferation in the multi-layer structure is easy to cross layers, that is, some cells will proliferate in the direction of the thickness of the patch instead of spreading along the orientation direction, which affects the cell proliferation to a certain extent.

[0166] (III) Cell migration assay:

[0167] Experimental methods:

[0168] 1. Cut the sample of Example 1 into a circular shape similar to the bottom of the 48-well plate, sterilize it, and soak it in MEM culture medium containing 10% FBS at 37° C. for 24 hours to allow the culture medium to fully soak into the sample.

[0169] 2. The whole process was performed in a clean bench to ensure aseptic operation. Mouse fibroblast L-929 cells grown to the logarithmic growth phase were digested with 0.25% trypsin (containing EDTA). After digestion, the cell suspension was centrifuged (1000 rpm, 5 min), the supernatant was discarded, and the cells were resuspended in MEM medium. After counting and dilution, 20×10 4 The soaked samples were spread in 48-well plates, and 3 samples were processed in parallel in each group.

[0170] 3. 20×10 4 50 μL of cell suspension per well was added to three 48-well plates. The cell suspension was uniformly added to the upper left corner of the 48-well plate. After 4 hours, an appropriate amount of culture medium was added to the plate wall. The amount of culture medium should just cover the sample (without affecting the position of the cells to prevent the complete evaporation of the culture medium and affect the cell viability). After 24 hours, 1 mL of culture medium was added to each well and added to the plate wall to avoid affecting the position of the cells. The cells were cultured in a cell culture incubator for 1, 3, and 6 days respectively.

[0171] 4. Cell staining and observation: When the sampling time point is reached, the culture medium in the well plate is aspirated and rinsed twice with PBS. After rinsing, 300uL of 10ug / mL acridine orange solution is added to each well for staining. Incubate at room temperature in the dark for 15-20min. After incubation, use a fluorescence microscope (excitation filter wavelength 488nm, blocking filter wavelength 515nm) to observe the cell proliferation or migration status at the upper left corner, upper right corner, lower left corner, and lower right corner of the electrospun membrane.

[0172] Experimental results:

[0173] Figure 3 This is a graph showing the cell migration results after the cells provided in Experimental Example 1 of the present invention were co-incubated with the degradable repair patch of Example 1 of the present application for 6 days.

[0174] Depend on Figure 3 It can be seen that the cells are evenly distributed on the oriented structured degradable repair patch of this embodiment, with a large number of cells distributed in the upper left corner, upper right corner, lower left corner, lower right corner and center of the patch. The cells show good migration behavior on the oriented oral repair membrane.

[0175] (IV) Degradation experiment:

[0176] Experimental methods:

[0177] (1) Preparation of enzyme buffer:

[0178] Prepare a solution containing potassium dihydrogen phosphate and disodium hydrogen phosphate with sterile double distilled water, containing 1.653g KH2PO4 and 7.744g NaH2PO4 per liter of buffer. The pH value of the buffer solution should be 7.4±0.2. After sterilization, add 0.2g / L lipase. The salts used in the preparation are analytically pure and dried to constant weight.

[0179] (2) Degradation test:

[0180] The sample is vacuum dried at room temperature to constant weight, and the weight of the sample is accurately measured. The sample is placed in a glass container, covered with enzyme buffer and the container is sealed. The minimum volume of the buffer should be 10 mL, and the ratio of the volume of the buffer (mL) to the mass of the sample (g) should be greater than or equal to 30:1. The sample is maintained at 37 ± 1 ° C in a constant temperature water bath or oven.

[0181] (3) Determination of degradation cycle:

[0182] For sample degradation testing, samples were taken at 12 weeks, 13 weeks, 14 weeks, 25 weeks, 26 weeks, 27 weeks, 35 weeks and 36 weeks for mechanical property testing.

[0183] After wiping the liquid on the sample surface with a paper towel, load the sample into the tensile testing machine fixture and test it directly. The test rate is set to 50mm / min. The test is terminated when the sample cannot be tested for mechanical properties, and the time point for stopping the test is the degradation cycle of the sample.

[0184] Experimental results:

[0185] sample Test cycle / week Example 1 13 Example 2 26 Example 3 35 Example 4 13 Example 5 35 Example 6 13 Comparative Example 1 13

[0186] It should be noted that tissue repair is a complex process that requires a certain amount of time to ensure that the damaged part can fully recover and regain sufficient strength and stability. If the patch degrades prematurely, it may lead to repair failure or the need for reoperation. If the patch exists in the body for too long, it may increase the risk of inflammation. Too long a degradation time may also affect the normal growth and repair process of surrounding tissues, and may also cause long-term compression of surrounding tissues or other adverse reactions.

[0187] From the above results, it can be seen that the degradable repair patch prepared by the present invention completely degrades within 13 weeks to 35 weeks, which can provide sufficient strength support for tissue repair to meet clinical needs, and does not exist in the body for too long.

[0188] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A degradable repair patch, characterized in that: The degradable repair patch is prepared by compounding multiple layers of fiber oriented sheets; The fiber orientation sheet is formed into oriented fibers by an electrostatic spinning method, and the orientation directions of the oriented fibers in the fiber orientation sheet are consistent; The diameter of the oriented fibers in the fiber orientation sheet is 1 nm to 20 μm, the porosity is 40 to 80%, and the thickness of the fiber orientation sheet is 0.05 to 0.95 mm; The orientation directions of the fibers in each layer of the fiber orientation sheets in the degradable repair patch are different.

2. The degradable repair patch according to claim 1, characterized in that: The oriented fibers are obtained by electrostatic spinning of degradable polyurethane or polylactic acid. Preferably, the weight average molecular weight Mw of the degradable polyurethane is 20W to 26W; Preferably, the weight average molecular weight Mw of the polylactic acid is 15W to 30W.

3. The degradable repair patch according to claim 1, characterized in that: The degradable repair patch has a thickness of 0.1-1 mm, a tensile strength of 10 N / cm-50 N / cm, a breaking elongation of 100%-800%, and a suture strength of 5 N-30 N.

4. The degradable repair patch according to claim 1, characterized in that: The multi-layer fiber oriented sheet includes 2 to 6 layers, preferably 2 layers.

5. The degradable repair patch according to claim 4, characterized in that: The degradable repair patch is prepared by compounding two layers of fiber-oriented sheets; Preferably, the two-layer fiber-oriented sheet comprises a first fiber-oriented sheet and a second fiber-oriented sheet, and the first fiber-oriented sheet and the second fiber-oriented sheet have different orientation directions and are at an angle of 90°±15°.

6. A method for preparing the degradable repair patch according to any one of claims 1 to 5, characterized in that: The preparation method comprises: S1: dissolving the degradable polyurethane in a solvent to obtain a spinning solution; S2: electrospinning the spinning solution to obtain a fiber orientation sheet A, then adjusting the electrospinning direction, electrospinning on the fiber orientation sheet A to obtain a fiber orientation sheet B intersecting the orientation direction of the fiber orientation sheet A, and obtaining a degradable repair patch composed of two layers of fiber orientation sheets; S3: repeat step S2 to obtain a degradable repair patch composed of multiple layers of oriented fiber sheets; Preferably, in step 2, the orientation directions of the fiber orientation sheet A and the fiber orientation sheet B are perpendicularly crossed at an angle of 90°±15°.

7. The method for preparing the degradable repair patch according to claim 6, characterized in that: The concentration of the degradable polyurethane in the spinning solution in step S1 is 5-25% (w / v); Preferably, the solvent in the spinning solution is a single solvent of N,N-dimethylformamide, a single solvent of N,N-dimethylacetamide, a mixed solvent of N,N-dimethylformamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether, or a mixed solvent of N,N-dimethylacetamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether; More preferably, the solvent in the spinning solution is a mixed solvent of N,N-dimethylformamide and tetrahydrofuran, wherein the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 10:1-3:7, wherein the preferred volume ratio is 10:1-1:

1.

8. The method for preparing the degradable repair patch according to claim 6, characterized in that: The conditions for electrospinning in step S2 include: Negative voltage: -1KV~-4KV, positive voltage: 8KV~10KV, injection speed of the nozzle: 0.05-0.6ml / min; rotation speed of the receiving device: (800, 2800)rpm / min, distance between the nozzle and the receiving device: 0~50mm; translation speed of the nozzle is (0, 500)mm / min.

9. The method for preparing the degradable repair patch according to claim 6, characterized in that: The preparation method further comprises: a step of removing the solvent from the prepared degradable repair patch.

10. Use of the degradable repair patch according to any one of claims 1 to 5 in the preparation of nerve tissue repair materials, vascular tissue repair materials, oral tissue repair materials and bone tissue repair materials.

Citation Information

Cited By

  • Double-layer composite patch with healing promoting and repairing functions and preparation method of double-layer composite patch

    CN120514916A

  • A double-layer composite patch with healing and repairing function and its preparation method

    CN120514916B

  • Medical repair film with orthogonal crack limiting structure and preparation method of medical repair film

    CN122351597A